Biochemical and haematological indicators of excessive alcohol consumption. - Chalmers, D M (1981)
Discriminant function analysis was used to determine the optimum combination of haematological and biochemical tests which gave the best discrimination between hospital patients with high and low alcohol intakes. We studied 265 patients with alcohol-related disease, 133 gastroenterology outpatients drinking less than 20 g of alcohol per day, and 104 patients with a variety of non-alcoholic liver disease. Values of mean cell volume (MCV), serum bilirubin, aspartate transaminase, serum alkaline phosphatase (AP) and gamma glutamyl transferase (gamma GT), serum albumin, serum globulin, and uric acid were determined in each patient. The best discrimination between the three groups of patients was provided by a combination of mean corpuscular volume, log10 gamma GT, and log10 serum alkaline phosphatase. In women, 92% of the high alcohol group, 100% of the low alcohol group, and 87% of the non-alcoholic liver disease were correctly allocated by the discriminant analysis. The corresponding figures for the men were 80%, 100%, and 71%. Thus, over 80% of patients with excessive alcohol intake were correctly allocated by the use of three simple laboratory tests.